The Mad Genius Stereotype: Still Alive and Well - Baudson, Tanja G. (Frontiers in Psychology, 2016)
Scientists and laypeople agree on high ability as a defining feature of giftedness. Yet their views on gifted people’s socioemotional characteristics diverge. Most studies find the gifted to be similar or slightly superior to average-ability persons in these domains (“harmony hypothesis”). However, subjective conceptions and media representations, most of which have focused on gifted children and youth, stress the socioemotional downsides of giftedness (“disharmony hypothesis”), affecting highly able individuals and those around them, thus hampering individual development. To date, most studies on gifted stereotypes have examined selective samples, mostly teachers. The present study is the first to provide representative data on conceptions of gifted individuals in general. A brief survey of 1,029 German adults assessed quality and prevalence of stereotypes about gifted individuals, without an explicit focus on children and/or adolescents. Latent class analysis revealed two conceptions of giftedness, with twice as many “disharmonious” than “harmonious” raters. Male gender, single parenthood, unemployment, higher income or negative attitudes towards the gifted predicted disharmonious ratings. However, effects were small, suggesting future studies look deeper into the processes of stereotype formation and maintenance.